Halo, kje si? - Bulc, Gregor (Javnost (Ljubljana), 2007)
The article discusses mobile phones in the context of power relations and surveillance in one's everyday-life experiences. Special interest is directed toward individuals' experiences of structural inequalities and relations of communication control in the light of blurring of the public/private division through extensive use of mobile phones. Based on ethnographic research and semi-structured interviews with service workers in Slovenia, it is argued thatprivate lives of non-material labour force are increasingly subject to interpersonal surveillance determined by power relations in neo-liberal/post-welfare state capitalism, which forces individuals to exercise particular oppositional strategies directed against their constant communicative availability to authorities. In this perspective, interpersonal communication can be plausibly seen as a threat to individualsć privacy and personal freedoms.
Keywords: communication; komuniciranje; medosebne komunikacije; vsakdanje življenje; zasebnost; privacy; mobilni telefoni; nadzor